Advances in Photocatalytic Nanocomposite Technology: Synthesis and Applications - Pujiastuti, Hendrini (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2024)
In wastewater treatment in particular, photocatalytic nanocomposites have shown great promise as a remedy for environmental contamination. Through the improvement of charge separation and the expansion of the spectral sensitivity to visible light, the synthesis of nanocomposites—which usually combine metal oxides like ZnO or TiO₂ with materials like carbon nanostructures or noble metals—improves photocatalytic performance. Sol-gel, hydrothermal, ion-exchange, and intercalation are some of the synthesis techniques that have been used to create these nanocomposites; each has its own advantages in terms of structural control and photocatalytic activity. Organic contaminants, including colors and medicinal chemicals, can be effectively degraded by photocatalytic nanocomposites. This overview covers the basic ideas of photocatalysis, how to create nanocomposite materials, and the latest developments in using photocatalytic nanocomposites for environmental cleanup. Making use of these resources provides a green, efficient, and sustainable approach to water purification, with future research focusing on improving their stability and scalability for industrial applications.